Transparansi Dalam Pelayanan Surat Izin Usaha Kecil Dan Menengah Pada Kantor Pelayanan Perizinan Terpadu Pada Kantor Pelayanan Perizinan Terpadu Kabupaten Kepulauan Sangihe. - LALO, MIRSADI; ROMPAS, WELSON; LONDA, VERRY (Sam Ratulangi University, 2014)
This study aims to documentation , cost and procedures that are still convoluted.Referring to the findings in this study , it is necessary not give advice as follows : The executive servicesnecessary to optimize the dissemination of the procedural requirements of licensing services to businessesthat trade transparency of services can be achieved optimally , efficiently , and effectively , and theexecutor of service should be improve performance should be more professional priority work ,transparency , accountability , and responsibility, and also no less important factor is the mentality andmorality .determine Transparency in service permit small and medium enterprises in the Integrated LicensingService Office Sangihe regency and the extent of satisfaction of service recipients Licensing , the datacollection was conducted through interviews with 15 informants consisting of : 1 the head office , 4 thefield of licensing services and 10 community service user permissions. In general , almost all indicators oftransparency services licenses held by its agencies viding less transparent in terms of time.Keywords : Transparency in Service License Small and Medium Size In Integrated Licensing ServiceOffice Sangihe regency .